Reading interests, reading habits and information needs of the urban poor in Constitution Hills, Quezon City a survey with the implication for providing library services for them - Viray, Jacoba DG (Institute of Library Science, University of the Philippines Diliman, 1987)
This is a survey of the residents of Constitution Hills in Quezon City to determine their reading habits and interests, occupational patterns, literacy level, educational attainment, sources of information, subject preferences and their response to the idea of putting up a library in the locality. A 25-item questionnaire was the main data gathering instrument administered to 300 respondents consisting of 53 young males, 97 young females, 26 adult males and 124 adult females, chosen randomly. The dominant means of livelihood for the menfolk (35 per cent) is carpentry and laundering (10 per cent), for the womenfolk.